Advances in mergers and acquisitions. Vol. 1 - Gregory, Alan, 1954-; Cooper, Cary L. (Emerald, 2000)
Introduction (C. Cooper, A. Gregory). The post merger performance puzzle (A. Agrawal, J.F. Jaffe). The influence of cultural compatibility within cross-border acquisitions: a review (R. Schoenberg). Integrating mergers and acquisitions: an international reseearch review (D.M. Schweiger, P.K. Goulet). Takeovers as a disclipinary mechanism? (R. Limmack). Corporate governance, corporate control and takeovers (S. Sudarsanam). Acquisition strategy and target resistance: a theory of countervailing effects of pre-merger bidding and post-merger integration (J. Harrison et al.). Managerial ownership and risk-reducing acquisitions (J. Doukas, M. Holmen). Mergers between professional service firms: exploring an undirected process of integration (L. Empson). Tales of trial and triumph: a narratological perspective on international acquisition (M.C. Gertsen, A.-M. Soderberg).
Keywords: Consolidation and merger of corporations.; elektronické knihy; electronic books